(untitled) (Baghdad Science Journal, 2006)
Conducted the study of the experimental conditions of the interaction of glass the visual Alpmuth containing 15% Mall of zinc with phosphoric acid ????? various degrees of thermal and clip areas prone to interact different way turntable